Clinical Profile of Peripheral Artery Disease of Patients Attending Shahid Gangalal National Heart Center, Janakpurdham, Nepal - Singh, Amit Kumar; Pradhan, Pranil Man; Shah, Rajesh Kumar; Mahaseth, Aditya (Journal of Nepal Health Research Council, 2024)
Background: Peripheral artery disease is an important vascular disease. There is an increased incidence of acute limb ischemia in cases of peripheral artery disease. Objective of this study was to assess the prevalence of peripheral artery disease among high-risk patients attending out patient department in Shahid Gangalal National Heart Center, Janakpurdham. Methods: A total of 386 high risk patients for Peripheral Artery Disease were included in the study. Informed consent was taken from patients undergoing the study. Patients underwent ankle brachial index calculation to make a diagnosis of peripheral artery disease. Patients having ankle brachial index of <= 0.9 was considered to have peripheral artery disease. Patients diagnosed with peripheral artery disease further underwent doppler study. Results: The study showed the prevalence of peripheral artery disease to be 17.4% among high-risk patients attending Shahid Gangalal National Heart Centre, Janakpurdham. The prevalence of peripheral artery disease was more in females as compared to male which was statistically significant. Most of the high-risk patients were patients with hypertension at Shahid Gangalal National Heart Centre. Conclusions: Peripheral artery disease prevalence is significant among high-risk patients attending Shahid Gangalal National Heart Centre, Janakpurdham. High risk patients should undergo evaluation of peripheral artery disease for early detection and treatment. Keywords: Ankle brachial index; chronic kidney disease; coronary artery disease; hypertension; peripheral artery disease.